2001
DOI: 10.1002/kpm.107
|View full text |Cite
|
Sign up to set email alerts
|

Gendering knowledge: the practices of knowledge management in the pharmaceutical industry

Abstract: Knowledge and knowledge management have become two of the latest buzzwords in the management literature. However, the literature presents primarily normative, undersocialized models of how knowledge could be administrated and developed as an organizational resource, and does not sufficiently recognize the social, political and emotional aspects of knowledge. In general, the knowledge of knowledge management is not situational. For instance, in what respect does the notion of knowledge take gender issues into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 57 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…Second, we have made a theoretical and empirical contribution to the field by bringing together the hitherto disconnected literatures relating to knowledge exchange and combination, IWB and gender. We have shown that the knowledge process itself is gendered (Styhre et al, 2001), and suggest that although women and men may exchange and combine knowledge to the same degree, women's segregation into lower-status and more routinised roles means that they are not able to translate this into innovative work behaviours, thus further depleting their career capital (Duberley and Cohen, 2010), and fostering a cycle of disadvantage for women in the knowledge economy. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, we have made a theoretical and empirical contribution to the field by bringing together the hitherto disconnected literatures relating to knowledge exchange and combination, IWB and gender. We have shown that the knowledge process itself is gendered (Styhre et al, 2001), and suggest that although women and men may exchange and combine knowledge to the same degree, women's segregation into lower-status and more routinised roles means that they are not able to translate this into innovative work behaviours, thus further depleting their career capital (Duberley and Cohen, 2010), and fostering a cycle of disadvantage for women in the knowledge economy. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, within these sectors women tend to be crowded into low-status, low-skill and often non-permanent peripheral occupations with few developmental opportunities, and to earn substantially less than men (Cross, 2009;Glover and Guerrier, 2010;Jubas and Butterwick, 2008;Kelan, 2007;Reid, 1998;Tharenou, 2005;Walby, 2011), despite statistics showing they possess comparable or higher levels of education and qualification (Bolton and Muzio, 2008;Jubas and Butterwick, 2008;Styhre et al, 2001) and the existence of equal opportunities legislation (d'Mello, 2006;Fisher, 2010;Stanworth, 2000). However, it has been found that women are somewhat more likely to be found in the higher level occupational groupings within KIFs than within the economy as a whole (Turner and McMahon, 2008;Walby, 2011).…”
Section: Women In Kifsmentioning
confidence: 99%
See 3 more Smart Citations